Anti-Ro and Concomitant Anti-La Autoantibodies Strongly Associated With Anti-oxLDL or Anti-Phospholipid Antibody in Systemic Lupus Erythematosus. Issue 8 (December 2016) - Kurien, Biji Theyilamannil; Fesmire, James; Anderson, Camille Jean; Scofield, Robert Hal
Abstract : Background: Premature atherosclerosis is observed in systemic lupus erythematosus (SLE). Oxidative modification of LDL is associated with atherosclerotic plaque formation. Objectives: We hypothesized that anti-oxidized LDL (oxLDL) and anti-phospholipid (APL) in SLE sera would segregate with specific antibody subsets, and that anti-oxLDL antibodies will linger in circulation over an extended period. Patients and Methods: Sixty-seven SLE and control subjects and two SLE subjects with sera collected longitudinally for 13 years were tested for anti-oxLDL and IgG/IgM/IgA APL antibodies. Results: Anti-oxLDL ELISA values above 57.48 Activity Units (AcU) (means of normals + 3 standard deviations) and anti-IgG/IgM/IgA APL above 10 phospholipid units (PU) were considered positive. Average anti-oxLDL was 67.7 ± 50.5 AcU in SLE compared to 23.9 ± 11.19 AcU in normals ( P = 0.018). Ten out of ten subjects with anti-Ro60/anti-La/anti-Ro52 antibodies had highly significant ( P < 0.0001) anti-oxLDL (127.29 ± 45.67 AcU) and IgG APL (18.66 ± 7.4 PU) ( P < 0.02). Subjects with anti-RNP were positive for anti-oxLDL ( P < 0.002), but subjects with anti-Ro60/anti-Ro52 and subjects negative for extractable nuclear antigen (ENA) antibody were not positive for anti-oxLDL. Anti-oxLDL/anti-IgG APL remained significantly elevated in two patients studied longitudinally. Interestingly, one developed anti-oxLDL/anti-APL antibodies several years before anti-Ro60 development. Conclusions: Presence of antibodies against Ro RNP and La, and RNP is highly associated with developing anti-oxLDL and APL antibodies in SLE. It will be clinically important to see if cardiovascular events occur in these SLE subsets having elevated anti-oxLDL and APL antibodies. Emergence of anti-oxLDL/IgG APL before anti-Ro60 over time in a patient indicates that these antibodies could not be cross-reactive in nature, at least in this particular patient.